Crystal structure of cyclohexylammonium thiocyanate - A. Bagabas, Abdulaziz; Alhoshan, Sultan B.; Ghabbour, Hazem A.; C. S., Chidan Kumar; Fun, Hoong Kun (International Union of Crystallography, 2015)
In the title salt, C6H11NH3 +SCN, the cyclohexylammonium ring adopts a slightly distorted chair conformation. The ammonium group occupies an equatorial position to minimize 1,3 and 1,5 diaxial interactions. In the crystal, the components are linked by N—H N and N—H S hydrogen-bonding interactions, resulting in a three-dimensional network.